2000
DOI: 10.1016/s0035-9203(00)90333-x
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis: acute and chronic disease, relapse and re-activation

Abstract: In melioidosis-endemic regions the importance of re-activation of Burkholderia pseudomallei from latent foci remains unclear. This topic was assessed in a 10-year prospective study (1989-99) of melioidosis in the tropical north of the Northern Territory of Australia, together with other aspects of the nature of melioidosis. Incubation period from defined inoculating events was previously ascertained as 1-21 (mean 9) days. Of 252 total cases 244 (97%) were considered to be from recent acquisition of B. pseudoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
202
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(211 citation statements)
references
References 26 publications
8
202
0
1
Order By: Relevance
“…The chronic form of the disease is evident from discovery at autopsy or by subsequent activation causing other forms of the disease. It is known that B. pseudomallei can enter a dormant state following initial infection or recovery from clinical disease [3], and that dormant cells can be triggered, leading to relapse or the onset of acute melioidosis [4]. The mechanisms underlying these different clinical manifestations and the triggers causing the more serious forms of the disease are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic form of the disease is evident from discovery at autopsy or by subsequent activation causing other forms of the disease. It is known that B. pseudomallei can enter a dormant state following initial infection or recovery from clinical disease [3], and that dormant cells can be triggered, leading to relapse or the onset of acute melioidosis [4]. The mechanisms underlying these different clinical manifestations and the triggers causing the more serious forms of the disease are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Earlier studies indicated that 13-23% of patients with melioidosis had such a recurrence and as high as onefifth of these recurrences could be fatal. 4,5 However, the choice and duration of antibiotic treatment to prevent these recurrences remains unsettled, as evidenced by several different regimen reported in the literatures during the last two decades. 5,8,[10][11][12]14 The currently recommended eradication therapy with the combination of cotrimoxazole and doxycycline, given for 12-20 weeks, has decreased the 1-year recurrence rate of culture-proven melioidosis to~6%.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, the choice and duration of antibiotic treatment to prevent these recurrences remains unsettled, as evidenced by several different regimen reported in the literatures during the last two decades. 5,8,[10][11][12]14 The currently recommended eradication therapy with the combination of cotrimoxazole and doxycycline, given for 12-20 weeks, has decreased the 1-year recurrence rate of culture-proven melioidosis to~6%. 8 In our study, the 5% recurrence rates in patients who had received this combination regimen drugs is comparable to that of the original clinical trial and the 3.2% culture-proven recurrence rate in recipients of cotrimoxazole alone is quite low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations